A rememoração nas imagens dos quilombos - Alessandra Pereira Brito (2021)
Based on the strength of black women and their relationship with the land and territory in films made in quilombos, the study seeks to understand how these productions enlighten the community’s memories. To contextualize the history of the quilombos, their forms of life, thought and political imagination, we dialogue with the perspectives of the intellectuals Beatriz Nascimento, Abdias Nascimento, Antônio Bispo dos Santos, Joelson Ferreira, Leda Maria Martins and Selma dos Santos Dealdina. Our argument describes the different gestures of rememoration in Tança (Irmandade dos Atores da Pândega and Associação Quilombola Mato do Tição, 2014), Pra se contar uma história (Elen Linth, Lucicleide Santos, Diego Jesus and Leandro Rodrigues, 2013), Quilombo Rio dos Macacos (Josias Pires, 2017), Nove Águas (Gabriel Martins and Quilombo dos Marques, 2019) and Aruanda (Linduarte Noronha, 1960).The filmic analyses reveal the presence of five expressive procedures that establish a quilombola becoming in contemporary Brazilian cinema: the performance, the paths through the territory, the testimony, the re-enactment and the presence of sonorities (the singing and the music).